(3TQM GdCLQhejIs - (3TgGH GdOjf CHh GdYHGS CMeO Hf CMeO GdQedi GdCfUGQj GdTGaYjs; (3GHf GLQhe , CHh YHO Gddg eMeO Hf eMeO Hf OGhO GdUfgGLj,J (B723 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdYdGe CeG HYO agPG JYdjb Ydi ebOeI GdTgjQ HGHf BLQhe HSe Gddg GdQMef GdQMje GdHGD eJYdbI HeMPha hGdGSe eTJb ef GdSeh s
(3BNQgG (B:s
(3hGdUaI GdeTHgI HGSe GdaGYdi , cgPG QLd MSf GdhLg hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3fSNI CNQi s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdfMhs